Understanding MMPI-2 response structure between schizophrenia and healthy individuals - Hsu, Yu Cheng; Ye, Zhiyu; Dai, Lisha; Jing, Yaqin; Tsui, Kwok-Leung; Yip, Paul S. F.; Li, Wentian; Zhang, Qingpeng (Frontiers in Psychiatry, 2022)
Background: Using Minnesota Multiphasic Personality Inventory-2 (MMPI-2) clinical scales to evaluate clinical symptoms in schizophrenia is a well-studied topic. Nonetheless, research focuses less on how do these clinical scales interact with each other. Aims: Investigates the network structure and interaction of the MMPI-2 clinical scales between healthy individuals and schizophrenics through the Bayesian network. Method: Data was collected from Wuhan Psychiatric Hospital from March 2008 to May 2018. A total of 714 schizophrenics and 714 healthy subjects were identified through propensity score matching according to the criteria of the International Classification of Diseases (ICD-11). Separated MMPI-2 clinical scales Bayesian networks were built for the healthy subjects and schizophrenics, respectively. Results: The Bayesian network showed that the lower 7 scale was a consequence of the correlation of the lower 2 scale and greater 8 scale. A solely lower 7 scale does yield neither lower 2 scale nor higher 8 scales. The proposed method showed 72% of accuracy with 78% area under the ROC curve (AUC), similar to the previous studies. Limitations: The proposed method simplified the continuous Bayesian network to predict binary outcomes, including other categorical data is not explored. Besides, the participants might only represent an endemic as they come from a single hospital. Conclusion: This work identified MMPI-2 clinical scales correlation and built separated Bayesian networks to investigate the difference between schizophrenics and healthy people. These differences may contribute to a better understanding of the clinical symptoms of schizophrenia and provide medical professionals with new perspectives for diagnosis.